Analisis Praktik Jual Beli Bola Bulu Tangkis Ditinjau Dari Perspektif Hukum Islam (Studi Kasus Di Gedung Hall Sk 10 Kelurahan Bandar Jaya) - Syahril Ramadhan; Haeran Haeran; Zeni Sunarti; Kurniawan Kurniawan; Alisyah Pitri; Reza Okva Marwendi; Ahmad Hidayat (Journal of Innovative and Creativity (Joecy), 2026)
This study analyzes the practice of buying and selling badminton shuttlecocks at the SK 10 Hall in Bandar Jaya Urban Village from an Islamic legal perspective. Employing a descriptive qualitative method, data were collected through in-depth interviews and direct observation involving sellers, buyers, hall management, and local religious figures. The results indicate that transactions are conducted directly using simple verbal agreements, with sellers honestly disclosing price and product quality information prior to the transaction. Viewed through the lens of *fiqh muamalah* (Islamic commercial law), this economic practice generally adheres to fundamental Sharia principles such as mutual consent, price transparency, and honesty between parties. However, a potential for minor *gharar* (uncertainty) remains regarding the durability and specific quality of the shuttlecocks in certain transactions. This study contributes to the development of Sharia economic law scholarship regarding micro-economic activities within community sports settings. Future research is encouraged to expand the scope of informants to ensure a comprehensive analysis.